A framework for South African university students' online learning: social presence, digital skills and competencies - Lubisi, Ntombizethu (My University, 2022)
Over the years, institutions of higher learning across the world have embraced the use of digital technology to facilitate learning. University students require digital skills and digital competencies to take full advantage of online learning. Additionally, one of the most important factors of students’ learning experience in an online environment is the sense of belonging. Students engaging in online learning geographically separated from their instructors and peers often feel isolated. The purpose of the study was to explore digital skills, digital competencies and social presence necessary for an effective South African university online learning. The study used the General Technology Competency and Use (GTCU) framework and the Social Presence Theory as a lens to explore the digital skills, digital competencies and social presence necessary for South African university online learning. A case study approach was used to study in-house first-year students in a South African university learning online. A mixed method research was selected due to its fitness to answer the proposed research questions. The data was collected via an online questionnaire and the semi-structured interviews at the University of the Witwatersrand in South Africa, Johannesburg. Quantitative data was analysed using descriptive statistics and the qualitative data was analysed using thematic analysis. Findings from the study indicated that the social-economic background does play an important role in in-house students learning online. The interaction was a challenge, participants felt isolated from their instructors which impacted their online learning experience. They did not feel a sense of belonging to their courses. The study will contribute to policies such as the South African National Development Plan (NDP) 2030 with the focus on lifelong learning, the United Nations (UN) Sustainable Development Goal 2030 goal 4. It will also contribute to the university learning and teaching policies where online learning is concerned as well as assist University improve their online learning offering. Our study links to information systems and online learning at universities.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Online learning; Digital skills; Digital Competencies